PENGARUH FRAKSI VOLUME DAN ARAH SERAT RAMI TERHADAP KEKUATAN IMPAK MATERIAL KOMPOSIT UNTUK APLIKASI BUMPER - Astuti, Fina Andika Frida; Arif Rochman Fachrudin; Mira Esculenta Martawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid growth of the automotive industry demands ongoing innovation in material engineering to improve vehicle performance and safety. The bumper, as a key structural component, must provide collision protection while supporting fuel efficiency and reducing environmental impact. A major challenge is producing bumpers that are both strong and lightweight, prompting exploration of composite materials. Among natural fibers suitable for composite reinforcement, ramie fiber is a promising candidate. Ramie fiber offers several advantages, including high mechanical strength and relatively low density. The objective of this study is to develop a composite material with high impact strength as an alternative bumper material. An experimental research method was employed, with composite fabrication carried out using the hand lay-up technique. The variables in this study included fiber orientation vertical, horizontal, and random. Volume fraction with variations of 30% fiber and 70% matrix; 45% fiber and 55% matrix; and 60% fiber and 40% matrix. The results indicate that both fiber orientation and volume fraction significantly affect impact strength. The lowest impact strength was observed in specimens with horizontal fiber orientation and a 30% fiber volume fraction, yielding 0.00719 J/mm². The highest impact strength was obtained from specimens with vertical fiber orientation and a 60% fiber volume fraction, reaching 0.05578 J/mm². Based on these findings, ramie fiber composites meeting the minimum impact strength standard for Toyota bumpers are those with a 60% fiber and 40% matrix composition, particularly with random or vertical fiber orientations.